The Pain in the Canon of Medicine: Types, Causes, and Treatment - Çetkin, Murat; Ergin, Gülbin; Alptuğ, Beraat; Kılıç, Ayşe; Özler, Necati (European Journal of Therapeutics, 2023)
Objective: Avicenna (980–1037 AD) was a renowned physician and philosopher. This study aimed to elaborate on the presented information in The Canon of Medicine about pain, its causes, types, and treatment methods in the pain-related specific chapters and compare it with today’s information. Methods: The information in the pain-related chapters in The Canon of Medicine was examined. This information was compared with the information in the English translation of the book. The information obtained by the correlation between the two works was compared with the current knowledge. Results: The pain was defined as abnormal condition seen in an animal’s body. The causes of pain were examined as sudden and irregular abnormalities in temperament and interruption of continuity. Avicenna categorized pain and developed hypotheses about the cause of each type of pain. The application of Avicenna’s pain treatment is based on the use of methods that act in opposition to the elements that cause loss of temperament and continuity. He prescribed analgesic agents, anesthetics, and antispasmodics for the pain relief. Conclusion: Although the effect of the pain-related theories of Hippocrates and Galen are also visible in The Canon of Medicine, his work contains much more detailed information about the definition, types, causes, and treatment methods of pain. The definitions he made in The Canon of Medicine about the classification of pain are found in many of the pain assessment scales used today. His descriptions of drug and dose selection are similar to those of modern pharmaceutical principles.